Regulatory Policy for Village Cooperatives: The KDKMP Model in Regional Development Planning - Faried, Annisa Ilmi; Maisyarah, Renny; Sari, Maya Macia; Fitriana, Yunita (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The establishment of Village/Sub-District Red and White Cooperatives (Koperasi Desa/Kelurahan Merah Putih/KDKMP) represents a transformative policy initiative in Indonesia's regional development framework (Thabit & Mora, 2023; Jamaluddin et al., 2023). This study examines the regulatory and institutional architecture governing KDKMP implementation and its implications for optimizing regional development planning across Indonesian districts. Utilizing a mixed-methods approach combining policy analysis, institutional assessment, and stakeholder consultations conducted from January to August 2025, this research evaluates the governance structures, funding mechanisms, and operational frameworks established under Law No. 3 of 2024 and Ministry of Finance Regulation No. 49 of 2025 (McNaught, 2024). The findings reveal that effective KDKMP implementation requires multi-stakeholder collaborative governance, strategic alignment with national development priorities including Asta Cita and SDGs, and capacity-building mechanisms for cooperative managers (Douglas & Ansell, 2023; Rodríguez-Pose et al., 2024). Analysis of 8,494 cooperatives established in East Java Province demonstrates that systematic regulatory frameworks correlate with accelerated economic empowerment, enhanced agricultural value chains, and improved financial inclusion in rural communities (Mohammadi et al., 2024). However, challenges persist including institutional capacity gaps, funding access limitations, and coordination inefficiencies between government levels. The study contributes a comprehensive regulatory framework model that integrates policy coherence, institutional strengthening, and participatory planning mechanisms to optimize KDKMP's role in regional development. These findings offer practical guidance for policymakers and development practitioners implementing cooperative-based development strategies in emerging economies.